Application of zeolite as a bacterial carrier in the self-healing of cement mortar cracks. (9th May 2022) - Yuan, Hao; Zhang, Qian; Hu, Xiangming; Wu, Mingyue; Zhao, Yanyun; Feng, Yue; Shen, Dingchen
Highlights: Sulphoaluminate cement coating can effectively protect microorganisms. The air permeability test was used to determine the effectiveness of crack healing. Microorganisms, nutrients and precursors can be integrated on zeolite. Abstract: Microbial induced calcite precipitation (MICP) technology can achieve the self-healing of concrete cracks; nevertheless, sustaining high biological activity is essential to the widespread deployment of this methodology. In the paper, the effect of zeolite microbial particles on the mechanical properties and crack healing effect of cement mortar was investigated using zeolite as a bacterial carrier. The findings revealed that the zeolite microbial particles generated by the sulphoaluminate cement coating were quite impermeable and retained intense urease activity even after treatment in a high alkaline environment. The microbiological zeolite particles improved the mechanical performance of mortar throughout the experimental dosing range, and the compressive strength only slightly dropped at 7.62% dosage. The healing rate of the crack area of the mortar sample was significantly improved after 28 d of curing; thus, the sample's water absorption, water permeability, and air permeability were reduced considerably, and further, the performance for related features were improved with the increase in dosage. The white precipitate formed in the crack area was identified as calcite by scanning electron microscope (SEM), energy dispersive spectroscopy (EDS), and X-ray diffraction (XRD) analysis. In summary, it can be concluded that zeolite can be used as an efficient carrier of mineralized bacteria to repair cement mortar cracks, maintaining the mechanical properties of concrete while maintaining the mineralization activity of strains and improving the healing effect of cracks. All the findings acquired within the scope of the study provide a theoretical reference for the widespread and intense adoption of MICP technology in the healing of concrete cracks.